Ensino remoto de geografia: desafios enfrentados pelos professores e alunos no cenário pandêmico da Covid-19 - Santos, Mayra Nayara Nair dos (2024)
In 2019, a virus that originated in Wuhan, China, crossed borders and infected people worldwide. As a consequence, the routine of millions of individuals had to be modified due to isolation and social distancing measures, aimed at preventing the spread of the virus and alleviating strain on healthcare systems worldwide. In the education system, there was a halt in in-person activities, and a transition to a model that, in Brazil, was referred to as Ensino Remoto Emergencial (Emergency Remote Teaching). Technological devices and connectivity were required for the classes to take place. Thus, in terms of relevance, the personal aspect stands out, which concerns the fact that, involved in a personal core of education professionals, it fueled the desire to understand how Geography professionals would be dealing with emergency remote teaching. As academic relevance, it is understood that this research will guide the development to understand learning in Geography Teaching within the contexts of emergency responses in a pandemic setting. The social and professional aspect involves the fact that other researchers can foster the relationship of an Emergency Geography, capable of being inserted into any social contexts. The aim of this research focuses on analyzing the historical-geographical context of the Covid-19 pandemic scenario between the years 2020 to 2022 and the didactic-pedagogical effects in the educational field at the high school level, for both teachers and second-year students of the Integrated High School to Technical Education program at the Instituto Federal de Educação, Ciência e Tecnologia do Piauí, located in Piripiri, Piauí. To achieve the objective, a qualitative participant-type methodology was chosen, with one research technique involving the use of a printed questionnaire that was distributed to 43 students who are part of the spatial focus of this investigation. In the bibliographic review, this research emphasizes Stefan (2021) and Ferraz (2020), which delve into the evolutionary process of humanity as narrated by viruses, emphasizing the significance of Geography in pandemic studies; Sampaio (2020) and Júnior (2020), who offer insights into the implementation of Emergency Remote Teaching in Brazil; and for educational perspectives, insights were drawn from Senhoras (2020), Góis (2020), and Silva (2020) to understand remote teaching and its educational demands. In Geography and Geography Education, the choice was made to highlight Cavalcanti (2010; 2012), Pontuschka (2018), and Brito (2022), who emphasize geographical aspects of the challenges in contemporary life. The research concluded that Emergency Remote Teaching exposed the socio-economic inequality that exists in Brazil and introduced, at the heart of education, significant gaps in the education system during the Coronavirus pandemic. In Geography, its utility shines as a significant research area for understanding geographical science. It has the capability to describe, analyze, point out, reference, engage in dialogue, and comprehend social events. In the Geography Education, the challenges brought about by this emergency situation triggered outdated processes in learning and education. At the core of this research, the problems and challenges faced by teachers and students had technological, educational, and instructional aspects in teaching and learning